Crystal structures of the Bacillus subtilis prophage lytic cassette proteins XepA and YomS. Issue 11 (6th November 2019) - Freitag-Pohl, Stefanie; Jasilionis, Andrius; Håkansson, Maria; Svensson, L. Anders; Kovačič, Rebeka; Welin, Martin; Watzlawick, Hildegard; Wang, Lei; Altenbuchner, Josef; Płotka, Magdalena; Kaczorowska, Anna Karina; Kaczorowski, Tadeusz; et al.
Abstract : The lytic cassette proteins XepA and YomS from Bacillus subtilis prophages have been characterized and it was found that only XepA establishes cytotoxic activity in plaque assays. The crystal structures of both proteins show a unique pentameric assembly, in which YomS adopts a very similar fold to the C‐terminal domain of the XepA dumbbell pentamer. The overall architecture of XepA, with the N‐terminal domain subunits resembling cytoplasmic membrane‐binding C2‐domain folds, suggests that any lytic functionality could be based on disruption of the proton motive force of the cytoplasmic membrane, which induces cell lysis. Abstract : As part of the Virus‐X Consortium that aims to identify and characterize novel proteins and enzymes from bacteriophages and archaeal viruses, the genes of the putative lytic proteins XepA from Bacillus subtilis prophage PBSX and YomS from prophage SPβ were cloned and the proteins were subsequently produced and functionally characterized. In order to elucidate the role and the molecular mechanism of XepA and YomS, the crystal structures of these proteins were solved at resolutions of 1.9 and 1.3 Å, respectively. XepA consists of two antiparallel β‐sandwich domains connected by a 30‐amino‐acid linker region. A pentamer of this protein adopts a unique dumbbell‐shaped architecture consisting of two discs and a central tunnel. YomS (12.9 kDa per monomer), which is less than half the size of XepA (30.3 kDa), shows homology to the C‐terminal part of XepA and exhibits a similar pentameric disc arrangement. Each β‐sandwich entity resembles the fold of typical cytoplasmic membrane‐binding C2 domains. Only XepA exhibits distinct cytotoxic activity in vivo, suggesting that the N‐terminal pentameric domain is essential for this biological activity. The biological and structural data presented here suggest that XepA disrupts the proton motive force of the cytoplasmatic membrane, thus supporting cell lysis.